Ideal pH for the adsorption of metal ions Cr6+, Ni2+, Pb2+ in aqueous solution with different adsorbent materials - Cruz-Lopes Luísa P. (De Gruyter, 2021)
Industrialization increases the number of heavy metals released into the environment. Lead (Pb2+), nickel (Ni2+) and chromium (Cr6+) are among these toxic metals and cause irreversible effects on ecosystems and human health due to their bio-accumulative potential. The decontamination through adsorption processes using lignocellulosic wastes from agricultural and/or forestry processes is a viable solution. Hence, this work aimed at studying the effect of pH on the biosorption of the metal ions using four different by-product materials: walnut shell, chestnut shell, pinewood and burnt pinewood. These experiments were conducted with solutions of the three heavy metals in which the adsorbents were immersed to measure the rate of adsorption. A range of pH values from 3.0 to 7.5 was used in the experiments, and the concentrations were determined by atomic absorption. The results showed different behaviour of the biosorbent materials when applied to the different metals. The lead adsorption had an ideal pH in the range of 5.5–7.5 when the walnut shell was used as an adsorbent, corresponding to values of adsorption greater than 90%, but for the other materials, maximum adsorption occurred for a pH of 7.5. For the adsorption of chromium, the pH was very heterogeneous with all adsorbents, with optimal values of pH varying from 3.0 (for chestnut shell) to 6.5 (for walnut shell and wood). For nickel, the best pH range was around pH 5, with different values according to the lignocellulosic material used. These results indicate that the tested biosorbents have the potential to decontaminate wastewater in variable extensions and that by controlling the pH of the solution; a more efficient removal of the heavy metals can be achieved.